1997
DOI: 10.1038/bjc.1997.87
|View full text |Cite
|
Sign up to set email alerts
|

DNA interstrand cross-linking and cytotoxicity induced by chloroethylnitrosoureas and cisplatin in human glioma cell lines which vary in cellular concentration of O6-alkylguanine-DNA alkyltransferase

Abstract: Summary Fifteen human glioma cell lines were examined for their sensitivity to 1 ,3-bis(chloroethyl)-nitrosourea (BCNU, carmustine) and cisdichlorodiamminoplatinum (cisplatin), the induction of DNA interstrand cross-linking (DNA-ISC) induced by the two agents and cellular 06_ alkylguanine alkyltransferase (ATase) activity. Cell lines differed in their sensitivities to BCNU by up to 12-fold and to cisplatin by up to 21 -fold. For both drugs, the extent of DNA-ISC was related to the drug sensitivity. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Moreover, of the MGMT-methylated tumors, there are only two glioblastomas, and one of these had only a biopsy (Case 6) whereas the other had a resection but was listed as NE, or not able to be evaluated (Case 9). Indeed, of the seven MGMTmethylated tumors, more (4) are listed as``not able to be evaluated'' than those that were evaluable (3). Thus it is difficult with such small numbers to come to a definitive conclusion.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, of the MGMT-methylated tumors, there are only two glioblastomas, and one of these had only a biopsy (Case 6) whereas the other had a resection but was listed as NE, or not able to be evaluated (Case 9). Indeed, of the seven MGMTmethylated tumors, more (4) are listed as``not able to be evaluated'' than those that were evaluable (3). Thus it is difficult with such small numbers to come to a definitive conclusion.…”
Section: Commentarymentioning
confidence: 99%
“…8,11,16) However, combination chemotherapy with CDDP or CBDCA and VP-16 as the second line chemotherapy following nitrosourea failure has shown encouraging results. 1,10,23) Furthermore, the antitumor activity of platinum compounds is not related to MGMT activity, 3,17) so platinum compounds are good candidates for the treatment of MGMT-unmethylated tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike O 6 ‐alkylguanine alkylating agents, there is a controversy existing between the MGMT activity and the cytotoxicity of CDDP. Although several studies have shown that the cytotoxicity of CDDP is correlated with expression levels of MGMT, certain studies have contradicted this finding . In addition, whether MGMT expression could impact the CDDP efficacy and the clinical prognosis in NPC patients has not been examined.…”
mentioning
confidence: 99%
“…Although several studies have shown that the cytotoxicity of CDDP is correlated with expression levels of MGMT, certain studies have contradicted this finding. [14][15][16][17][18] In addition, whether MGMT expression could impact the CDDP efficacy and the clinical prognosis in NPC patients has not been examined. In this study, we investigated cellular responses and explored mechanistic analyses between MGMT expression and CDDP in NPC cells; we also analyzed the clinical significance of MGMT expression in NPC patients treated with CDDP-based CCRT.…”
mentioning
confidence: 99%
“…The platinum agents as well as temozolomide and O 6 -benzylguanine can abrogate MGMT activity (22). Several studies have also shown that the antitumor activity of platinum agents is not affected by MGMT activity (23)(24)(25). This knowledge has led to Phase II clinical trials with promising results (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%